Plantas americanas nuevas para la flora adventicia del sur de España. - Bartoli, Adriana; Sánchez Gullón, Enrique; Weickert, Pedro; Tortosa, Roberto D. (Acta Botanica Malacitana, 2007)
New data about american neophytes for southern Andalusian flora. Palabras clave. Corología, xenófitos americanos, especies invasoras, Andalucía, SO de España. Key words. Chorology, american xenophytes, invasive flora, Andalusía, SW Spain.